Prevalence, patterns and predictors of metabolic abnormalities in Nigerian hypertensives with hypertriglyceridemic waist phenotype: A cross sectional study. - Casmir E Amadi; Amam C Mbakwem; Dolapo C Duro; Ifeoma C Udenze; Clement M Akinsola; Jayne N Ajuluchukwu; David A Wale Oke (Public Library of Science (PLoS), 2022)
Background Simultaneous presence of elevated waist circumference and hypertriglyceridemia (HTGW) is a simple and low-cost measure of visceral obesity, and it is associated with a plethora of cardio-metabolic abnormalities that can increase the risk of cardiovascular diseases and incident Type 2 diabetes mellitus. We decided to study the prevalence, patterns, and predictors of metabolic abnormalities in Nigerian hypertensives with the HTGW phenotype. Methods The medical records of 582 hypertensives with complete data of interest were retrieved and analyzed for the study. Their socio-demographic data, anthropometric data, and booking blood pressure values were retrieved. The results of their fasting plasma glucose, lipid profile, uric acid and serum creatinine were also retrieved for analysis. Results The mean age of the study population was 56.2 ±13.6, with 53.1% being males. The prevalence of smoking and use of alcohol was 4.3% and 26.5% respectively. The prevalence of the HTGW phenotype was 23.4% and were predominantly males (61%). Subjects with the HTGW phenotype were more obese assessed by waist circumference (WC) and body mass index (BMI). Mean serum total cholesterol, triglyceride, very low-density lipoprotein, uric acid, and creatinine were significantly higher in the HTGW phenotype (p = 0.003; <0.001; <0.001; 0.002 and <0.001 respectively). The prevalence of newly diagnosed Type 2 diabetes was 28.7%. There was also a preponderance of cardio-metabolic abnormalities (obesity, dyslipidaemia, hyperuricemia) in the HTGW phenotype. In both males and females, the HGTW phenotype was significantly associated with elevated Tc, TG, VLDL, hyperuricemia and atherogenic index of plasma. Conclusion The HTGW phenotype is common amongst Nigerian hypertensives, and it is associated with metabolic abnormalities.